Identification and Characterization of cry Genes Coding for Insecticidal Crystal Protein in Bacillus thuringiensis JC 590 - Yaowaluk Poojitkanont; Suttipun Keawsompong; Jariya Chanpaisaeng (Agriculture and Natural Resources, 2008)
The detection of cryI, cryII and cryV genes in chromosomal and plasmid DNA of Bacillus thuringiensis JC 590 was done using polymerase chain reaction (PCR). The PCR products were cloned, sequenced and subject to BLAST search at NCBI. The results revealed that 5 genes of cry1 namely cry1Ab, cry1C, cry1D, cry1E and cry1I and 1 gene of cry2 namely cry2A were in both chromosomal and plasmid DNA. The full length DNA sequence of cryIC was cloned by PCR walking technique, sequenced, and analyzed. The result showed that the chromosomal cry1C gene consisted of 3,507 bp encoded for 1,169 of amino acid and the plasmid DNA cry1C gene had 3,450 bp encoded for 1,160 of amino acid in length. Sequence comparison with other cry1C genes in database at NCBI showed these sequences had highly homology with cry1C genes in other B. thuringiensis strains. The investigation of cry 1C in B. thuringiensis JC 590 could be the basic knowledge for future application in biocontrol because of its high toxicity.